COMPARATIVE STUDY OF SOCIAL ADVERTISING IN UZBEK AND ENGLISH IN VARIOUS DIRECTIONS (Eureka Journal of Language, Culture & Social Change, 2026)
The article highlights the fact that today social advertising serves as an active tool that fully affects a wide audience in eliminating important social problems in society. In particular, in order to highlight the lexical-syntactic and pragmatic features of social advertisements in Uzbek and English, a comparative analysis was carried out, dividing them into several areas.
Keywords: Advertising, social, society, expression, problem, direction, public organization, population, information, English, Uzbek, language, discussion, communication